Virtual Film Forum in teacher training: didactic experience with Primary Education students at the University of Costa Rica’s Rodrigo Facio Headquarters (Innovaciones Educativas, 2021)
The systematization of this work presents the results of the evaluation carried out by the participating students in the didactic experience Virtual Film Forum, carried out in the Rural Education course and the single-teacher school at the University of Costa Rica. It all happened when faced with the need to replace a face-to-face immersion educational tour in the rural single-teacher school context due to the pandemics caused by the virus responsible for COVID-19. To carry out this work, we adopted a socio-critical approach and benefited from critical pedagogy. The concepts of didactic strategy and portfolio of evidence we readdressed to discuss the advantage of the Virtual Film Forum. In addition, aspects of the single-teacher school and the teacher are described. Within the framework of qualitative research that studies the perspective of the student body participating in the experience, the main results showed that: despite the students not being immersed in the desired performance context, the virtual experience was successful in attaining the outlined objective; it also facilitated, through participatory social dialogue, the construction of a learning community where it was possible to share knowledge, experiences, and concerns regarding the reality of the rural single-teacher school. That sequence of activities innovates in University teaching practice and can be adapted to various courses and learning contexts in the educational domain.
Keywords: Vocational training; Rural education; primary school teacher; Educational strategies; Online learning; COVID-19